ANALISIS KESALAHAN BERBAHASA PADA SPANDUK DAN PAPAN REKLAME SEBAGAI MEDIA PROMOSI - Herwani, Suci; Inti Khatun Nafia (Universitas Terbuka, 2024)
Banners and billboards are promotional media that are widely used by people to promote their businesses. It is not uncommon for the words or sentences used to influence the reader. However, many banner and billboard makers ignore the rules of writing. This research aims to analyze language errors on banners and billboards in Kudus Regency. The research method used is descriptive qualitative. The research data is the use of Indonesian on banners and billboards. The data analysis technique uses the intralingual matching method. The research results found several language errors on banners and billboards including standard word errors, writing foreign terms, writing abbreviations, and writing numbers. By knowing the language errors that arise, it can help writers to be more careful in their writing and must follow the rules or writing rules in the guidelines.